Measurement of Liquid level by Using A Novel Fibre Optic Sensor - Das, Sarmistha; Haloi, Rupjyoti; Sarma, Kanak Chandra (International Journal of Computer Sciences and Engineering, 2025)
With the recent developments in sensors and instrumentation engineering, there is a growing application of optical fibre as sensor for the measurement of various parameters like pressure, temperature, liquid level, humidity, displacement, volume etc. Over the years, there has been a great deal of interest on the development of liquid level sensors using ﬁbre optics. Measurement of liquid level is important for various industrial and laboratory applications and ﬁbre optic sensors are ideal for such purposes. Optical fibres are preferred over other conventional measuring techniques for such measurements due to its inherent advantages such as light weight, small size, low power, resistant to electromagnetic interference, high sensitivity, wide bandwidth, multiplexing advantages, geometrical flexibility and environmental ruggedness. Moreover, with the ready availability of optoelectronic components, fabrication cost of ﬁbre optic sensors has drastically come down in the last two decades. In this paper, we are presenting an intensity modulated fibre optic sensor which is low in cost and capable of continuously monitoring and measuring the volume of different types of liquids with high degree of repeatability which can be calibrated with level. Here the intensity modulated technique has been chosen for measuring liquid level as it is simple and of low cost.